The asset value of franchising - Sichel, Debora Lacs (Research Papers of Wrocław University of Economics, 2018)
Franchising is perceived as a marketing concept used to expand business. The paper discusses the development of franchising agreements in the context of the expansion of a trademark from a local or national level to international markets. It aims at determining how the economic integration has contributed to the development of franchising agreements. The author focuses on the fashion industry and analyses two different international brands: H&M and Zara, taking into account their market targets and international expansion
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 109-122
Keywords: trademark; internationalization; consumer; intangible assets; znak towarowy; internacjonalizacja; konsument; aktywa niematerialne